Improved Far-Field Angle in Narrow-Ridge High-Power Laser Diodes Using a Double Stripe Structure - Daehong Kim; Jung-Tack Yang; Woo-Young Choi; Younghyun Kim (IEEE Photonics Journal)
We propose a novel double stripe structure for achieving a narrow far-field angle without significant output power loss in narrow-ridge high-power broad-area laser diodes. By introducing double SiO2 stripes on the top side of the laser diode, we effectively suppress high-order modes through mode weight engineering. Through self-consistent electro-thermal-optical simulations powered by LASTIP with the well-verified model from the reference, we comprehensively analyze and compare the characteristics of high-power broad-area laser diodes utilizing the loss tailoring technique that adopted the much simpler structure compared to prior study and our proposed structure. Our results demonstrate a significant reduction of approximately 36% in the far-field angle while maintaining slope efficiency. This approach shows promise for enhancing the performance of coupling efficiency between narrow-ridge high-power laser diodes and fibers.